Preparing effective business plans : an entrepreneurial approach / Bruce R Barringer - Barringer, Bruce R.
"Authorized adaptation from the United States edition, entitled Preparing effective business plans: an entrepreneurial approach, 2nd edition, ISBN 978-0-133-50697-6 by Bruce R. Barringer published by Pearson Education © 2015"